1997
DOI: 10.2172/515537
|View full text |Cite
|
Sign up to set email alerts
|

Risk reduction and the privatization option: First principles

Abstract: TheJIEE vision is to be an internationdyrecognizedresearchbased institute solving key problems at the interface of energy, environment, and economics.The JIEE mission is to harness and enhance the collective resources of the Oak Ridge National Laboratory, the Tennessee Valley Authority, and the University of Tennessee, to create synergy among partners, and to attract and assist outstanding professionals in order to find solutions to key national and international E3 issues.Onefocus area of the JIEE is biomass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Early experimental studies revealed that hypothetical referenda were likely to generate biased estimates of willingness to pay at the aggregate level (Cummings et al [1997]). They argued that modifications to the survey design, such as cheap talk or learning designs (Bjornstad et al [1997]; Cummings and Taylor [1999]), were capable of mitigating this bias.…”
Section: Experiments and Cvmmentioning
confidence: 99%
See 1 more Smart Citation
“…Early experimental studies revealed that hypothetical referenda were likely to generate biased estimates of willingness to pay at the aggregate level (Cummings et al [1997]). They argued that modifications to the survey design, such as cheap talk or learning designs (Bjornstad et al [1997]; Cummings and Taylor [1999]), were capable of mitigating this bias.…”
Section: Experiments and Cvmmentioning
confidence: 99%
“…Bias at this level is an issue of incentive compatibility and reflects an individuals' propensity to demand reveal under an elicitation mechanism or question (Burton et al [in press]). These authors review a number of studies (Vossler and Kerkvliet [2003]; Brown et al, 2003, Cummings andTaylor [[1999]]; Bjornstad et al [1997]) incorporating both induced value experiments 8 and comparisons between field surveys and actual voting behavior find little evidence of bias in hypothetical referenda at the aggregate level, but bias remaining at the individual level. It appears, therefore, that that the evidence regarding the reliability of hypothetical surveys is mixed.…”
Section: Experiments and Cvmmentioning
confidence: 99%